A catalytic-immune OGP peptide-crosslinked 3D-printed hydrogel scaffold for concurrent antitumor therapy and bone regeneration - Jiachen He; Jianjun Wu; Lin Wang; Siwei Yin; Kun Yu; Yanyun Liu; Dejia Xu; Tuo Ji; Yuzhi Gao; Yikuan Du; Xuzhu Gao; Limin Cai; et al. (Advanced Composites and Hybrid Materials, 2026)
Abstract Resection of bone-metastatic tumors is often accompanied by severe bone erosion and structural defects. Three‐dimensional (3D) printed hydrogel scaffolds with tailorable architectures and mechanical robustness are increasingly employed to restore bone integrity after tumor removal. Here, a 3D-printed sodium alginate/GelMA hydrogel scaffold is engineered to remodel the local microenvironment for simultaneous tumor ablation and bone repair, aiming to overcome the persistent challenge of functionally modifying hydrogel scaffolds to achieve both effective tumor eradication and bone regeneration. The scaffold encapsulates dendritic cell-derived exosomes loaded with the STING agonist Cyclic dinucleotide (Dex-CDN), together with methacrylated osteogenic growth peptide (OGP-MA), while a dopamine–manganese coordination nanozyme (DM) forms a mussel‐inspired catalytic coating on the surface. Under the acidic tumor milieu, DM exhibits peroxidase‐like activity to trigger Fenton reactions, deplete glutathione, and induce oxidative stress–mediated tumor cell death. Under physiological conditions, DM displays superoxide dismutase‐ and catalase‐like activities, scavenging reactive oxygen species and maintaining redox homeostasis to promote osteogenesis. Sustained Dex‐CDN release activates STING signaling and elicits potent antitumor immunity, whereas OGP‐MA triggers BMP/Smad‐mediated osteogenic differentiation. This integrated scaffold unites catalytic therapy, immune activation, and osteoinduction, offering a promising strategy for localized tumor control and bone regeneration following bone metastatic tumor resection.